DDRE-03. INTERNATIONAL PRECLINICAL DRUG DISCOVERY AND BIOMARKER PROGRAM INFORMING AN ADOPTIVE COMBINATORIAL TRIAL FOR DIFFUSE MIDLINE GLIOMAS. (9th November 2020) - Przystal, Justyna; Yadavilli, Sridevi; Abadi, Christina Coleman; Yadav, Viveka Nand; Laternser, Sandra; Cosentino, Chiara Cianciolo; Waszak, Sebastian; Cartaxo, Rodrigo; Biery, Matt; Myers, Carrie; Jayasekara, Samantha; Olson, James; et al.
Abstract: INTRODUCTION: DMG-ACT (DMG- multi-arm A daptive and C ombinatorial T rial) aims to implement a highly innovative clinical trial design of combinatorial arms for patients with diffuse midline gliomas (DMGs) at all disease stages that is adaptive to pre-clinical data generated in ten collaborating institutions. Novel drug and drug combination were tested, predictive biomarkers were identified and incorporated in clinical trial design. METHODS: In vitro (n=15) and in vivo (n=8) models of DMGs across ten institutions were used to assess single and combination treatments with ONC201, ONC206, marizomib, panobinostat, 5-Azacytidine, Val-083, GDC0084 and TAK228. In vivo drug toxicity screenings were conducted using larval zebrafish model and murine PDX models. Predictive biomarkers for ONC201 and ONC206 were identified using meta-analysis, and extensive molecular assays including CRISPR, RNAseq, FACS, and IHC. RESULTS: Inhibitory concentrations (IC50 ) were established and validated multiple preclinical models. ONC201 and ONC206, ONC201 and TAK228, ONC201 and GDC0084 showed synergism. In vivo survival assays showed increased survival for: ONC201 (p=0.01), ONC206 (p=0.01), ONC201+ONC206 (p=0.02), and ONC201+panobinostat (p=0.01). Marizomib showed toxicity in murine/zebrafish PDXs models. Murine pharmacokinetic analysis showed peak brain levels of ONC201 and ONC206 above pre-clinical IC50 . Molecular testing and analyses of existing drug screen across 537 cancer cell lines validated mitochondrial protease ClpP and ATF4 as ONC201/6 targets. Predictive biomarkers of response to drug were identified. CONCLUSION: Thorough preclinical testing in a multi-site laboratory setting is feasible and identified ONC201 in combination with ONC206, TAK228 and GDC0084 as promising therapeutics for DMGs.